Hyaluronidase Inhibitor in the Fruit of Citrus reticulata BLANCO - YOKOTA, MASAMI; SUGIYAMA, KAZUMI; MASUI, TOSHIO; NAKAGOMI, KAZUYA; YAMAMOTO, MASATOSHI; KATAYAMA, HARUKI; MAEDA, YUMIE; SUGIYAMA, KIYOSHI; OKADA, NAGAHISA (Eisei kagaku, 1991)
Fifty percent of ethanolic extracts from the immature fruits of Citrus reticulata BLANCO, C. tamurana hort. ex TANAKA, C. natsudaidai HAYATA and C. unshiu MARKOVICH showed a significant inhibitory effect on the activation of inactive hyaluronidase induced by compound 48/80. This effect decreased with the maturation of the fruit in all cases. Among the citrus fruits tested, the extract from the immature C. reticulata BLANCO showed the strongest inhibitory effect. The data of gel permeation chromatography and gas chromatography-mass spectrometry showed the hyaluronidase inhibitor in the fruit to be a pectin with a molecular weight of 1.1×105. The content of D-galacturonic acid in the pectin was determined to be 58% using the carbazole method. The pectin showed almost the same inhibitory effect (IC50 : 91 μg/ml) as a commercial pectin from oranges or a current anti-allergic agent, disodium cromoglycate. Hyaluronidase has been suggested to be one of the target enzymes controlling the degranulation of mast cells, and the inhibitory effect on the activation of inactive hyaluronidase has been reported by Kakegawa et al. (Chem. Pharm. Bull. 33 [1985]) to be an index of anti-allergic activity. Therefore, it is expected that the pectin in C. reticulata BLANCO might possess anti-allergic potential.